O PROJETO REGIONAL ROTA DOS TROPEIROS: UMA ANÁLISE DE PALMEIRA -PARANÁ - Schnell, Dieniffer Taline (2013)
The Project Regional Route Tropeiros launched in 2004, comes from the perspective of the National Tourism Regionalization, which had as main objective to decentralize tourism,promoting its regionalization, in this case covering 16 municipalities of Campos Gerais,Paraná. Among those municipalities whose origins were founded by their transition from the old Way of troops, is Palmeira part of this project. Thus, this research work aims to understand the relationship between the city and the project in question, checking their particularities, such as your physical Cultural Heritage, the implementation process and project development and optical municipal policy on tourism . In addition to research data pre-existent, this paper presents a collection of data obtained through interviews (with city government officials, councilors, Commercial and Industrial Association, the Association of Municipalities of Campos Gerais and others involved), and questionnaires conducted with general population to understand the relationship established between them and the development of the project in the municipality. However from this study realized a few factors that presents difficulties for consolidation in Palmeira Project (PR), among them are the lack of population and lack of incentive on the part of municipal administrators.